On the relationship between corruption and political ideology: the case of South Korea. - Kim, Hyun Jong; Lim, Sol; Kim, Tae-Hwan; Kim, Yunmi (Asia Europe Journal, 2025)
This article empirically investigates the relative effectiveness of political regimes liberal versus conservative in combating corruption in South Korea. Two corruption indices, the Corruption Perceptions Index (CPI) by Transparency International and the Worldwide Governance Indicators (WGI) by the World Bank, are employed to measure corruption levels. Through mean difference analysis and regression analysis, some strong and consistent empirical evidence emerges, suggesting that the liberal regime might have proven more effective in combating corruption in South Korea than its conservative counterpart, assuming that the perceived levels of corruption, as measured by both CPI and WGI, serve as reasonable approximations of the actual level of corruption.